Mathematical models for understanding dengue fever - Puerta-Yepes, María Eugenia (2025)
The most effective way to reduce the impact of Aedes aegypti continues to be to mitigate its presence in endemic areas. However, efforts in several countries have not succeeded in curbing its expansion. The exclusive use of chemical control carries risks to human health and promotes resistance in mosquitoes, while the release of Wolbachia-infected mosquitoes requires complementary actions of prevention and community participation. In this context, mathematical models are fundamental tools for designing comprehensive control strategies as they allow the identification of optimal conditions to determine the most appropriate times and places for chemical, biological, mechanical interventions or vaccination campaigns, and to understand the joint dynamics between the mosquito population and the exposed human population. In addition, these models can contribute to the development of early warning systems and formulate evidence-based public policies. This book provides guidelines for public health decision making through the formulation of mathematical models that guide the selection of control strategies and the analysis of key issues in epidemiology.